Thinking Trajectory of Students with Thinking and Feeling Personality Types in Solving Algebra Problems - Handican, Rhomiy; Laswadi; Jamaris Jamna; Solfema (Jurnal Pedagogi dan Pembelajaran, 2023)
The strategies students use in solving mathematical problems are quite diverse, so they affect students' personality types. This research focuses on analyzing the trajectory of students' thinking in solving algebraic problems in terms of thinking and feeling personality types. This research is qualitative research with a descriptive method. The population is 34 students; the sampling is done by purposive sampling—data collection techniques through personality questionnaire sheets, algebraic test questions, and interviews. Qualitative data analysis was done through data reduction, display, and conclusion/verification stages. The results showed that the students' thinking path in solving algebraic problems in terms of thinking and feeling personality types is that in the problem analysis cycle, thinking students can correctly show what is known from the problem. The problem-solving process is made sequentially up to the simplification cycle. In the completion cycle, students think until they get the final answer by completing the steps properly and correctly. Based on these results, students need help solving algebra problems properly compared to students with the thinking personality type. It is because students feel that the steps could be more sequential in solving problems with algebraic forms, and it is difficult to consider based on right or wrong (objective). Therefore, sometimes he needs to be more wishy-washy or even needs clarification in taking a stand.